The effect of isotropic roughness on the thermohydrodynamic solution of finite journal bearings - Che Hassan Che Haron; Nik Abdullah Nik Salleh (1991)
Thermohydrodynamic (THD) analysis of finite journal bearings with isotropic roughness is presented. A modified version of the Reynolds equation which includes surface roughness effects is solved using the Successive-overRelaxation method (SOR). 7he Swift-Stieber cavitation boundary condition was implemented in solving the Reynolds equation. The effects of various operating parameters as well as roughness parameters on the thermohydrodynamic of finite journal bearing are investigated and the results are compared with the smooth surface solutions. Along with the bearings geometries, the roughness characteristics, such as the variance ratio, should be included as design parameters in order to accurately predict the performance of hydrodynamic bearings